Preparation and characterization of polysaccharide-based nanoparticles with anticoagulant activity - da Silva LC (Dove Medical Press, 2012)
Luiz Cláudio da Silva,1 Thiago Garcia,1 Michela Mori,2 Giuseppina Sandri,2 Maria Cristina Bonferoni,2 Priscila V Finotelli,1 Leonardo P Cinelli,1 Carla Caramella,2 Lúcio M Cabral11Drug Department, Rio de Janeiro Federal University, Rio de Janeiro, Brazil; 2Department of Drug Sciences, University of Pavia, Pavia, ItalyAbstract: The aim of this study was to produce and characterize nanoparticles (NPs), combining chondroitin sulfate (CS) and fucoidan (FC) with chitosan for therapeutic purposes. These NPs were characterized by dynamic light scattering, zeta potential determination, and transmission electronic microscopy. The anticoagulant activity was determined for FC NPs and compared with FC solution at the same concentration. FC NPs showed regular shapes and better anticoagulant activity than free polysaccharide solution. FC solution did not affect coagulation compared to FC NPs, which increased up to two-fold, even at a lower concentration. Cytotoxicity and permeability tests were conducted using Caco-2 cell monolayer, exhibiting no toxic effect in this cell line and higher permeability for NP2 samples than FC solution at the same concentration.Keywords: nanoparticles, chitosan, chondroitin sulfate, fucoidan, aPTT, Caco-2